A new type photodiode: p-Si/GaN pn junction in series with GaN/Ag Schottky diode - Yakuphanoğlu, Fahrettin; Shokr, F. S.; Gupta, R. K.; Al-Ghamdi, Ahmed A.; Bin-Omran, S.; Al-Turki, Yusuf; El-Tantawy, Farid (Elsevier Science Sa, 2015)
Large quantities of gallium nitride (GaN) nanoparticles were successfully synthesized via a facile sol-gel approach. X-ray diffraction analysis confirms the polycrystalline nature of the GaN with hexagonal wurtzite structure and lattice constants a = 0.3189 nm and c = 0.5185 nm. The morphology of the GaN film was investigated by field emission scanning electron microscopy. The obtained results indicate that the synthesized GaN nanorods have an average length of around 60 nm and an average diameter of 23 nm. The optical band gap of the GaN film was obtained to be 3.4 eV. The gallium nitride/p-Si Schottky diode was fabricated by thermal evaporation technique on p-silicon. The current-voltage (IeV) characteristics of the fabricated diode was tested under dark and various light intensities. T The diode ideality factor and barrier height were computed using forward bias IeV characteristics of the diode and are found to be 1.66 and 0.53 eV, respectively. The obtained results suggest that the film preparation by sol gel method is fast and simple to prepare GaN based photodiode by according to metal organic deposition methods. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: GaN; Sol-gel; Schottky diode; Photodiode; Capacitance